Incidence of Endodontic Flare-up in Diabetic and Normal Individual: A 100 case study (Update Dental College Journal, 2019)
Diabetic mellitus is a burning issue in medical ground. If Pulp or periapical pathology develops on diabetic patient, it may need extra attention to manage by root canal treatment. Because very often diabetic patients develop hyperglycemia, leading complex immune response and enhanced virulence of certain microorganism and commonly cause exaggerbration of inter appointment clinical complain like, pain and swelling known as flare-up. The purpose of this study was to clinically examine the development of endodontic flare-up following endodontic intervention in control and in diabetic patient group. In the present study, overall incidence of inter-appointment flare-up in diabetic patients was found to be 19% whereas in non-diabetic group, incidence was 8% that was almost half to the diabetic group. So, this study conclude that root canal treatment can be comfortably done in controlled diabetic patient but need extra care during endodontic treatment if the patient is suffered from uncontrolled diabetes mellitus.Update Dent. Coll. j: 2019; 9 (2): 3-6